Interactive Effect of Ralstonia solanacearum on Lethal Wilt of Chili Caused by Phytophthora capsici - Leksomboon, Chalida; Chatchawankanphanich, Orawan; Suwanwongse, Sirilak (Agriculture and Natural Resources, 2012)
Ralstonia solanacearum and Phytophthora capsici are important soil-borne pathogens associated with lethal wilt symptoms on chili. Both pathogens were found in the same ﬁ eld in Thailand and caused serious disease in north Thailand. The local strains RS1/3 of R. solanacearum (RS) and PC4-1 of P. capsici (PC) were used for investigation of the interactive effect of R. solanacearum on the lethal wilt of chili caused by P. capsici. Chili cultivar CA365 (spur chili), Thaevee60 (hot chili) and commercial cultivar Sabun Nga (spur chili) were inoculated with PC4-1 or RS1/3 alone and by co-inoculation or sequential inoculation. In sequential inoculation, plants were inoculated with RS1/3 prior to PC4-1 by 3, 5 and 7 d. The results showed that PC4-1 was more aggressive than RS1/3 in all tested cultivars, and plants inoculated with both pathogens or PC4-1 alone had signiﬁ cantly more mortality in a shorter time. Plants which were inoculated with both pathogens or PC4-1 alone had total plant death at the same time, while with RS1/3 this occurred prior to PC4-1 by 5 and 7 d (13 d after RS1/3 inoculation). The results also showed that RS had no effect on plant death in the CA365 cultivar (susceptible to PC) when inoculated with RS1/3 prior to PC4-1 by 5 and 7 d. Different results showed in the Thaevee60 cultivar which was moderately resistant to PC and it was found that plants inoculated with RS1/3 prior to PC4-1 by 5 d had total plant death in a shorter time than when there was concomitant inoculation with both pathogens. Treatment of PC alone did not kill all plants whereas treatment of PC and RS concomitantly and of RS prior to PC by 5 d produced total plant death 27 and 24 d after RS inoculation. In the treatment of RS prior to PC by 7 d, all plants had died 24 d after RS inoculation whereas the application of PC alone or of PC and RS concomitantly did not kill all plants. This study indicated that RS enhanced the infection of the moderately resistant cultivar Thaevee60 by PC. In sequential inoculation, total plant death was apparent in the treatment of RS prior to PC by 3 d taking a longer period than in the treatment of RS and PC inoculated concomitantly. There was apparent antagonism between the two pathogens. When PC and RS were paired on a growth medium of potato dextrose agar, the mycelial growth of PC grown alone was signiﬁ cantly different from the mycelial growth of PC grown together with RS. These results were found in all 11 tested strains of RS.